Shaping up and fitting in : a grounded theory of women's body image : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Hamid, Jennifer (Massey University, 1995)
The present study employed a qualitative approach informed by a feminist perspective, specifically the generative, inductive methods of grounded theory to explore women's experiences regarding their body image. Reports of 11 women's experiences were obtained using a semi-structured interview framework. This study aimed to explore the cognitive, behavioural and psychological dimensions of women's body concerns, focusing on weight, shape, size and appearance; how these concerns affect the women; and what the women perceive as having contributed to their concerns. The preliminary grounded theory developed suggests that each of the women, to various degrees, monitor, evaluate, regulate and/or alter their bodies in specific ways, in order to maximise positive feelings about themselves, and minimise negative ones. The model developed in this study is process oriented and suggests that for most of the women, being happy with their bodies, or not feeling unhappy with them, is only a transitory part of an ongoing cyclical process of monitoring and regulating. These findings have important implications for education and prevention, and for 'treatment'. They also suggest many worthwhile avenues for future research.
Keywords: Body image; Psychological aspects; Women; Psychology